The social history of Ashab Al-Jawiyyin and the hadith transmission in the 17th century nusantara - Qudsy, Saifuddin Zuhri; Prasojo, Zaenudin Hudi; Ahmad Rafiq,; Teuku Zulfikar, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This article investigates the role of Ashab al-Jawiyyin in the spreading of hadith in the nusantara in the 17th century. It is an interesting topic since the ulama of hadith from Indonesia to Mecca then come back to Indonesia they can assimilate with the indigenous culture of Indonesia. By departing from the data described by Azra, we explore how the role of ashab al-jawiyyin has significant contribution in the spread of hadith in Indonesia. We argue that, the ideas brought by Ashab al-Jawiyyin were influenced by middle east Muslim scholars who have interdisciplinary scientific competence. The intersection of tariqa with a network of hadiths met through the sanad. Sanad, in both disciplines occupies a very central position. It then maintained the network structure both in the tariqa and in the transmission of hadith. Starting from Syibgatullah (1606) then Ahmad Syinwani (1619), Ahmad al-Qusyashi (1661), Ibrahim al-Kurani (1690), Abdullah bin Shaykh al-‘Aydarus (1663), Ba Shayban (1656), and Isa al-Maghribi (1669), they are the key main networks that made ashab al-Jawiyyin existed. The figures mentioned above are the majority figures of tariqa, hadith, sharia, fiqh and ushul fiqh. From Nuruddin al-Raniry and Abdurrauf al-Singkili that in which later from them the transmission of the distribution and writing of hadith began to be recorded well in the hands of their generations.